2018
DOI: 10.1111/ajt.14754
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus exposure and the occurrence of cytomegalovirus DNAemia after allogeneic hematopoietic stem cell transplantation

Abstract: Sirolimus appears to protect against cytomegalovirus (CMV) in organ transplant recipients. The effect of this drug in allogeneic hematopoietic stem cell transplantation recipients remains unexplored. By means of multivariate continuous-time Markov model analyses, we identified 3 independent covariates that significantly impacted the risk of CMV DNAemia: recipient/donor CMV serostatus, tacrolimus exposure, and sirolimus exposure. CMV-seropositive recipients with CMV-seronegative donors had a significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
1
13
1
Order By: Relevance
“…We previously observed that higher sirolimus concentrations had an inhibitory effect on CMV replication by reducing the probability of detectable CMV DNAemia at any level after RIC-allo-HSCT [11]. The present study confirms that higher sirolimus exposure also translates into a clinical benefit by reducing the probability of preemptive anti-CMV therapy in a larger multicenter cohort of RIC-allo-HSCT recipients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We previously observed that higher sirolimus concentrations had an inhibitory effect on CMV replication by reducing the probability of detectable CMV DNAemia at any level after RIC-allo-HSCT [11]. The present study confirms that higher sirolimus exposure also translates into a clinical benefit by reducing the probability of preemptive anti-CMV therapy in a larger multicenter cohort of RIC-allo-HSCT recipients.…”
Section: Discussionsupporting
confidence: 86%
“…We previously demonstrated that higher sirolimus exposure significantly reduced the risk of detectable CMV DNAemia at any level after allo-HSCT [11]. Our next step was to explore whether higher sirolimus concentrations could also have the clinical benefit of reducing the number of CMV DNAemia events necessitating preemptive antiviral therapy in allo-HSCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…In comparing CNI-based GVHD prophylaxis with CNI +mTORi-based approaches, the latter was associated with less CMV infection. There are data to suggest that mTORi may protect against CMV infection [21], although 2 randomized trials of CNI/methotrexate versus CNI/mTORi reported no differences in CMV infection incidence between treatment arms, with similar rates of GVHD between the arms [22,23]. However, the relationship between GVHD onset/ treatment and CMV infection was not examined for differences between arms in either trial [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Cyclosporine and tacrolimus, with or without methotrexate or mycophenolate mofetil (MMF), are by far the most common agents given in association with PTCy in different allo-HSCT scenarios. 2,4,5 However, sirolimus (Sir) with MMF has recently emerged as an alternative option to calcineurin inhibitor (CNI)-containing approaches, since it has an apparently more favorable toxicity profile [6][7][8] with encouraging results. 9,10 The aim of the present study was to retrospectively compare the clinical outcomes of adults with acute leukemia or myelodysplastic syndrome (MDS) undergoing myeloablative allo-HSCT from matched sibling donors (MSD) or unrelated donors at three institutions with two different strategies for GVHD prophylaxis, ex vivo TCD by CD34+ selection and unmanipulated grafts with PTCy-Sir-MMF.…”
Section: Introductionmentioning
confidence: 99%